EVALUASI AKUNTABILITAS RENCANA KERJA DAN ANGGARAN GUNA MENDUKUNG INOVASI RSUD. Dr. ISKAK TULUNGAGUNG - Mukti Prabowo, Rachmad Gesah (Program Doktor Ilmu Ekonomi, 2020)
The main purpose of this study is to explain the accountability of planned activities and budgets at General Hospital Dr. Iskak Tulungagung and its relationship withinnovations and programs implemented at the hospital. This research use desciptivequalitative approach. The results obtained from this study are that work plan and budgetaccountability has a positive impact on hospital managerial and operational performance.All forms of innovation and programs implemented by hospitals cannot be separated fromadequate planning and budgeting support.Keywords: Accountability, Work Plan and Budget, Innovation and Program